Global versus local environmental impacts of grazing and confined beef production systems - Modernel P; Astigarraga L; Picasso V (IOP Publishing, 2013)
Carbon footprint is a key indicator of the contribution of food production to climate change and its importance is increasing worldwide. Although it has been used as a sustainability index for assessing production systems, it does not take into account many other biophysical environmental dimensions more relevant at the local scale, such as soil erosion, nutrient imbalance, and pesticide contamination. We estimated carbon footprint, fossil fuel energy use, soil erosion, nutrient imbalance, and risk of pesticide contamination for five real beef background-finishing systems with increasing levels of intensification in Uruguay, which were combinations of grazing rangelands (RL), seeded pastures (SP), and confined in feedlot (FL). Carbon footprint decreased from 16.7 (RL–RL) to 6.9 kg (SP–FL) CO2 eq kg body weight−1 (BW; 'eq': equivalent). Energy use was zero for RL–RL and increased up to 17.3 MJ kg BW−1 for SP–FL. Soil erosion values varied from 7.7 (RL–RL) to 14.8 kg of soil kg BW−1 (SP–FL). Nitrogen and phosphorus nutrient balances showed surpluses for systems with seeded pastures and feedlots while RL–RL was deficient. Pesticide contamination risk was zero for RL–RL, and increased up to 21.2 for SP–FL. For the range of systems studied with increasing use of inputs, trade-offs were observed between global and local environmental problems. These results demonstrate that several indicators are needed to evaluate the sustainability of livestock production systems.